CUSTOMER SERVICE STRATEGY IN INCREASING THE NUMBER OF CUSTOMERS AT BANK BJB SYARIAH BRAGA BRANCH OFFICE - Hanif Achmad Rasyid Jauhari; Mujahid Shiroth Rasyid Jauhari (Journal of Public Administration, 2022)
Very tight competition in the world of banking services business has forced banking service companies to compete for the hearts of customers. Every company wants to maintain its presence in customers in order to survive and expand market share. To be able to entering the market, the company is required to meet customer needs by improving services. Bank bjb Syariah Braga Branch Office preparing staff employees who are able to handle their customers, which is usually called customer service. Customer service has the main task of providing services and fostering good relations with customers, therefore Bank bjb Syariah Braga Branch Office makes a special strategy so that customers feel comfortable so that it affects the number of customers who come to the office because of the services provided by customer service. The problem in this research is how the strategy of customer service in providing services to customers and the efforts that affect customer service at Bank bjb Syariah Braga Branch Office. The purpose of this research is to determine the strategy of customer service in providing services to customers and the efforts that affect customer service at Bank bjb Syariah Braga Branch Office. In this study the authors used qualitative research by using this research to produce descriptive data. Overall, it can be concluded from this research that it shows that the customer service strategy in providing services to customers, namely, competence (competence), trusted & trust (trust and be trusted), honesty (honesty), service excellent (excellent service), and innovation (change). As well as the efforts made by customer service in increasing the number of customers, the first is seven new accounts in one day, the second is cross selling, the third is roll play and the last is shopper. Thus, based on the results of this study, it is expected that the customer service of Bank bjb Syariah Braga Branch Office can improve good service to customers.